IN SITU OXYGEN ISOTOPE ANALYSIS WITH AN EXCIMER LASER USING F2 AND BRF5 REAGENTS AND O2 GAS AS ANALYTE - Rumble D.; Farquhar J.; Young E.D.; Christensen C.P. (My University, 1997)
In situ oxygen isotope analysis of silicate minerals has been validated by interlaboratory calibration using an excimer laser (KrF fill gas, 248 nm), F2 gas fluorinating reagent, and O2 gas as mass spectrometer analyte. A value of δ18OSMOW = 5.82%% (+/-0.03, 4 analyses) was obtained for almandine UWG-2 compared to a recommended value of 5.8%% (Valley et al., 1995). The interhalogen BrF5 was tested by comparing in situ analyses made alternatively with either BrF5 or F2 gas on crystals of almandine, epidote, forsterite, tourmaline, and zircon. Results for different pressures of BrF5 (20 to 40 torr) in the reaction chamber show that δ18O values decrease by 1 permil for an increase of 10 torr in BrF5 pressure. In strong contrast, δ18O values measured with purified F2 gas are precise and accurate over a range of from 15 to 150 torr F2 gas pressure. Use of F2 gives higher yields of O2 than with BrF5. Values of δ17O and δ18O measured in situ on a variety of silicates all plot on the terrestrial mass fractionation line, provided that NF3 contamination is eliminated from the O2 gas analyte.